Does promoting research advance planning in a general elderly population enhance completion of a research directive and proxies' predictive ability? a randomized controlled trial. Issue 3 (2nd July 2016) - Bravo, Gina; Trottier, Lise; Dubois, Marie-France; Arcand, Marcel; Blanchette, Danièle; Boire-Lavigne, Anne-Marie; Guay, Maryse; Hottin, Paule; Lane, Julie; Bellemare, Suzanne; Painter, Karen
ABSTRACT: Background : Communicating wishes regarding future research participation in the event of incapacity may help others make enrollment decisions that are more consistent with these wishes. We tested whether an advance planning intervention (1) motivated older adults to document their wishes regarding future research participation and (2) guided proxies in making hypothetical research decisions that agreed with those of the older adult.Methods : This randomized trial involved 235 dyads of older adults and proxies. The experimental intervention consisted of a group information session on advance directives, coupled with two encounters with a facilitator who helped older adults communicate their wishes to their proxy. Control participants attended three educational workshops on healthy behaviors. Short descriptions of hypothetical studies were used at baseline and twice post intervention to elicit older adults' and proxies' decisions regarding study enrollment. Answers were elicited under four health states of increasing cognitive impairment.Results : By the end of the trial, 80% of older adults allocated to the experimental group had recorded their preferences; 61% indicated a willingness to participate in clinical research should they be solicited after losing decisional capacity. At baseline, percentages of agreement on enrollment decisions ranged from 63% for a blood draw in the older adult's current health state to 24% for a dementia drug trial. From baseline to the second posttest, agreement increased in the experimental group while declining among controls. The positive effect of the intervention was restricted to the severe dementia health state, with agreement rising from 26 to 37%.Conclusions : The intervention motivated older adults to document their preferences regarding future research involvement. It had little effect on proxies' ability to make hypothetical research decisions that match those of the older adult. It remains to be seen whether documented preferences would facilitate substitute decision making in hypothetical and actual research situations.